The Physical Quality of Landrace Pork Which Aging in The Traditional Way - M. T., Tena; Sriyani, N. L. P.; Suarta, I G. (Jurnal Peternakan Tropika; Vol 8 No 1 (2020): Issue 8 No. 1 (2020); January - April, 2020)
This study aims to determine the effect of traditional meat aging on the physical quality of Landrace pork and the optimal length of time for traditional meat aging to get good quality pork. The research material used landrace pork loin on LD (Longisimus Dorsi). The design used was Completely Randomized Design (CRD) with four treatments and four replications, namely P0 = fresh meat that was not aging, P1 = meat aging the muscle part of LD (Longisimus Dorsi) during 8 hours, P2 = meat aging the muscle part LD (Longisimus Dorsi) during 16 hours, P3 = meat aging the muscle part of the LD (Longisimus Dorsi) during 24 hoursat room temperature 28-29 0 C. The variables observed in this study were pH measurement, meat color, water holding capacity, cooking loss, weep loss. The results showed that the traditional foraying statistics of Landrace pork crosses were significantly different (P <0.05) on pH value, meat color, water holding capacity, cooking loss, weep loss. The conclusion of this study is that Landrace pork crossing can improve the physical quality of crossing Landrace pork. The optimal length of pork delivery time to produce good quality pork for 8 hours for the color of red meat and high water holding capacity with cooking loss and low weep loss.   Keywords: traditional aging, pork, quality of pork, water holding capacity, cooking loss